Assessment of Hepatoprotective Activity of Justicia adhatoda L. Herbal Extracts Using Carbon Tetrachloride Influenced Hepatotoxicity in Rats Model. - Gaurav Kumar Sharma; Sarita Sharma (International Journal of Pharma and Bio Sciences, 2021)
The home grown medications, utilized in Indian frameworks of meds, are, in any case, being professed to be compelling and good for liver infection. The current examination has endeavored to exhibit the hepatoprotective movement of different natural concentrates of Justicia adhatoda L. by CCl4 incited hepatotoxicity in the Albino rats (Wister strain). The parameter like enzyme study (SGOT, SGPT, SALP, Serum bilirubin (total and direct) with histopathological studies have been carried out and the extent of regenerative changes have been observed. It was observed that the Chloroform concentrate of Justicia adhatoda L. at 200mg/kg of body weight indicated a critical decrease in raised degree of SGOT, SGPT, SALP and bilirubin. While the Petroleum ether and Aqueous concentrate showed moderate decrease in catalyst level. Ethanol concentrates did not show any huge decrease in protein level, demonstrating no movement. The hepatoprotective movement was upheld by minuscule histopathological assessment of liver tissue. Since after effects of biochemical investigations of blood tests of carbon tetrachloride rewarded rodents indicated critical increment in the degrees of serum compound exercises, mirroring the liver injury brought about by CCl4 and blood tests from the creatures rewarded with the Chloroform concentrate of Justicia adhatoda L. have demonstrated critical abatement in the degrees of serum markers, showing rewarded liver have been found to have noticeable hepatocytes with increasingly regenerative movement, which implies better hepatoprotective action when contrasted with different gatherings. Though Petroleum ether and Aqueous concentrate of Justicia adhatoda L. rewarded liver found to have the moderate level of greasy changes, which demonstrated moderate hepatoprotective action when contrasted with different gatherings. Considering the eventual outcomes of various biochemical boundaries, all the arrangements have demonstrated important hepatoprotective development for all intents and purposes indistinguishable with LIV-52.The best hepatoprotective activity was found with Chloroform concentrate of Justicia adhatoda L.